2012
DOI: 10.1371/journal.pone.0045843
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Passive and Active Particles in the Cell Nucleus

Abstract: Inspite of being embedded in a dense meshwork of nuclear chromatin, gene loci and large nuclear components are highly dynamic at C. To understand this apparent unfettered movement in an overdense environment, we study the dynamics of a passive micron size bead in live cell nuclei at two different temperatures ( and C) with and without external force. In the absence of a force, the beads are caged over large time scales. On application of a threshold uniaxial force (about 10 pN), the passive beads appear to ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 38 publications
4
63
0
Order By: Relevance
“…In this paper, we study the positioning and shape dynamics of a deformable inclusion embedded in a confined active gel. Formulated in this general way, our study is applicable to a variety of in-vivo and in-vitro contexts -(i) the positioning and shape fluctuations of the nucleus (or other localized organelles) within a cell [4][5][6][7][8], (ii) the dynamics of large colloidal particles embedded in an active medium [9][10][11][12], (iii) the positioning and dynamics of nuclei in multi-nucleated cells [13], (iv) the positioning and segregation of chromosomes within a nucleus [14][15][16][17] and (v) the fluctuations of a cell / cell-junction within a developing tissue [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we study the positioning and shape dynamics of a deformable inclusion embedded in a confined active gel. Formulated in this general way, our study is applicable to a variety of in-vivo and in-vitro contexts -(i) the positioning and shape fluctuations of the nucleus (or other localized organelles) within a cell [4][5][6][7][8], (ii) the dynamics of large colloidal particles embedded in an active medium [9][10][11][12], (iii) the positioning and dynamics of nuclei in multi-nucleated cells [13], (iv) the positioning and segregation of chromosomes within a nucleus [14][15][16][17] and (v) the fluctuations of a cell / cell-junction within a developing tissue [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Together, these mechanisms have crucial effects on the positioning and dynamics of various organelles in the cell. There have been significant advances in experimental techniques and theory on the use of optically trapped or injected beads to probe the mechanical properties of cells and the intracellular dynamics (1)(2)(3)(4)(5). In a number of microrheological studies of living cells that used microinjected particles as probes (6), the large-scale properties of the cytoplasm were estimated using multiparticle correlation studies due to the difficulty of introducing large particles into the cell.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to expectations, recent experiments have shown that fluctuations of nuclear components (eg. membrane or DNA loci) are not governed by intra-nuclear activity, but rather by the extra-nuclear actomyosin contractility [4][5][6][7][8][9].In this Letter, we introduce a simple model based on active gel theory [10-12] which illustrates how variation of active stress noise can induce a maximum in the fluctuation spectrum of the nuclear shape. We discuss the rather unexpected experimental result of Ref.[7] which, combining drug treatments and geometric constraints, shows that the nuclear area fluctuations are maximal for an intermediate level of contractility.…”
mentioning
confidence: 99%